Cx43 overexpression is involved in the hyper-proliferation effect of trichloroethylene on human embryonic stem cells. (15th January 2022) - Xia, Ying; Jiang, Bin; Teng, Zhongkun; Liu, Tiantian; Wang, Jianming; Aniagu, Stanley; Zhang, Guoxing; Chen, Tao; Jiang, Yan
Graphical abstract: Highlights: TCE exposure affected the proliferation of human embryonic stem cells. TCE treatment resulted in Cx43 overexpression. TCE-induced Cx43 upregulation was attributed to PI3K/Akt activation. Cx43 overexpression increased the expression of CDK2, responsible for cell proliferation in human embryonic stem cells. Abstract: Trichloroethylene (TCE) is a major environmental contaminant. Maternal exposure of TCE is linked to developmental defects, but the mechanisms remain to be elucidated. Along with a strategy of 3Rs principle, human embryonic stem cells (hESCs) are regarded as most promising in vitro models for developmental toxicity studies. TCE interfered with hESCs differentiation, but no report was available for TCE effects on hESCs proliferation. Here, we aimed to explore the toxic effects and mechanisms of TCE on hESCs proliferation. Treatment with TCE, did not affect the pluripotency genes expression. However, TCE enhanced hESCs proliferation, manifested by increased cell number, PCNA expression and EdU incorporation. Moreover, TCE exposure upregulated the protein expression levels of Cx43 and cyclin-dependent kinases. Knockdown of Cx43 attenuated the TCE-induced cell hyper-proliferation and CDK2 upregulation. Furthermore, TCE increased Akt phosphorylation, and the inhibition of Akt blocked the TCE-induced Cx43 overexpression and cell proliferation. In conclusion, TCE exposure resulted in upregulation of Cx43 via Akt phosphorylation, consequently stimulated CDK2 expression, contributing to hyper-proliferation in hESCs. Our study brings to light that TCE stimulated the proliferation of hESCs via Cx43, providing a new research avenue for the causes of TCE-induced developmental toxicity.